KEMITRAAN MODEL HELIK ANTARA PERGURUAN TINGGI, SMK DAN INDUSTRI OTOMOTIF UNTUK MENINGKATKAN KOMPETENSI SISWA - Meiyaldi Eka Putra; Teguh Irawan; Bintha Ustafiano; Fajar Maulana; Yolana Nursyafti (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: Higher education plays a crucial and strategic role in relation to the focus of national development, specifically the economic and human resource sectors. This study utilizes a qualitative approach and development in the field of education, utilizing Focus Group Discussions (FGDs) as the primary data collection technique. This study utilized a qualitative approach, utilizing Focus Group Discussions (FGDs) as the primary data collection technique. These FGDs allowed researchers to explore in-depth perspectives from participants through dynamic group interactions. The FGDs yielded a hypothetical model depicting the synergistic relationship between the three primary vocational education entities. The LPTK plays a role in providing the foundations of entrepreneurial competencies and automotive engineering skills, as well as shaping students' self-confidence and character. The validation results for the development of the Triple-Helix partnership model in preparing vocational students showed a high level of feasibility, with an overall score of 87%, categorized as suitable for use with revision. The development of a vocational student preparation model is based on a triple-helix partnership. The triple-helix partnership is based on a partnership between LPTK, SMK, and DUDI (industrial and industrial sectors). The key factor in the success of this model is the foundation of the partnership, a memorandum of understanding (MoU) between the three parties.  Keywords: Vocational student development, triple-helix partnerships   Abstrak: Perguruan Tinggi mempunyai peran penting dan strategis apabila dikaitkan dengan titik berat pembangunan nasional yaitu sektor ekonomi dan sumberdaya manusia. Melalui peningkatan peranan dan pembangunan dibidang pendidikan ini diwujudkan sumber daya manusia, Penelitian ini menggunakan pendekatan kualitatif dengan metode Focus Group Discussion (FGD) sebagai teknik utama pengumpulan data dengan pendekatan studi eksploratif kualitatif. FGD dipilih karena memungkinkan peneliti untuk menggali perspektif mendalam dari partisipan melalui interaksi kelompok yang dinamis. dari FGD menghasilkan sebuah model hipotetik yang menggambarkan hubungan sinergis antar tiga entitas utama pendidikan vokasional. LPTK berperan dalam memberikan dasar-dasar kompetensi keahlian wirausaha dan keahlian teknik otomotif, serta membentuk kepercayaan diri dan karakter Siswa. Hasil validasi terhadap pengembangan model kemitraan Triple-Helix dalam penyiapan siswa vokasional menunjukkan tingkat kelayakan yang tinggi dengan skor keseluruhan sebesar 87%, yang berada pada kategori layak digunakan dengan revisi. pengembangan  model penyiapan siswa vokasional berbasis kemitraan triple-helix. Kemitraan triple-helix didasarkan pada kemitraan antara Perguruan Tinggi LPTK, SMK, dan DUDI. Faktor yang menjadi kunci keberhasilan model ini adalah landasan kemitraan berupa nota kesepahaman (MoU) antara ketiga pihak tersebut. Kata kunci : Perkembangan siswa vokasional, kemitraan triple-helix